Magnetic-Fluorescent Responsive Janus Photonic Crystal Beads for Self-Destructive Anti-counterfeiting - Chen, Yiping (Langmuir : the ACS journal of surfaces and colloids, 2022)
In this study, we fabricate magnetic-fluorescent responsive Janus photonic crystal beads (JPCBs) based on poly(styrene-methyl methacrylate-acrylic acid) (p(St-MMA-AA)) colloidal nanoparticles, Fe3O4, and photobase generators used for self-destructive anti-counterfeiting. We synthesize two kinds of photobase generators that can react with fluorescamine to produce various fluorescence colors. A microfluidic method is used to obtain the Janus photonic crystal beads. The upper portions of the JPCBs are photonic crystals assembled with colloidal spheres, whereas the Fe3O4 settles down to the bottom of the JPCBs due to its higher density. Photobase generators are distributed in photonic crystal gaps. Because of the magnetism of the Fe3O4, the JPCBs could be flipped from one side to the other in the presence of a magnet. After being exposed to UVC light and fluorescamine, the JPCBs can fluoresce under UVA light. Then, we create Janus microbeads arrays with various types of beads and apply them to the visitor card, bracelet, and box label to provide irreversible and self-destructive anti-counterfeiting. The JPCBs are capable of being encoded and angle-independently displayed, which are crucial to their applications in anti-counterfeiting, information coding, and array display